Tuberculosis and other urogenital infections as sexually transmitted diseases - E. V. Kulchavenya (Вестник урологии, 2023)
The analysis of domestic and foreign literature on the epidemiology, etiology, and possible sexual transmission of urinary tract infections (UTI) was carried out. It has been established that more than 30 pathogens are currently classified as sexually transmitted infections (STI). The molecular genetic method has shown the identity of uropathogenic Escherichia coli in familial cases of UTI, which confirms the sexual route of infection transmission, which was not previously classified as a classic STI. Several works are cited that undoubtedly testify to the possible sexual transmission of Mycobacterium tuberculosis. Up to date, few reports of sexual transmission of UTI have been published, although tuberculosis is one of the most common infectious diseases worldwide. Perhaps because the partner of a patient with genital tuberculosis or other UTI is not actively evaluated. Thus, the possibility of sexual transmission may be underestimated. Sexual transmission of M. tuberculosis as well as uropathogenic E. coli is unlikely, but possible.